Interaction of sodium dodecyl sulfate and triton X-100 with ofloxacin drug using conductivity and UV–visible spectroscopic techniques in aqueous alcohols media at several temperatures - Ahmed, Bulbul; Anjum, Kahkashan; Alfakeer, M.; Hossain, Md. Shahadat; Hasan, Kamrul; Rana, Shahed; Hoque, Md. Anamul (Colloids and surfaces. A, Physicochemical and engineering aspects, 2024)
The current investigation explores the association and complexation of the mixture of anionic surfactant, sodium dodecyl sulfate (SDS), and antibiotic drug, ofloxacin (OFC) as well as nonionic surfactant, Triton X-100 (TRX) and OFC drug respectively in several additive solutions. The investigations were performed by applying conductivity and UV-Visible spectroscopic techniques. The impacts of drug concentration, types of solvents, and composition of aq. solutions of alcohols (methanol (MeOH), ethanol (EtOH), and 1-propanol (1-PrOH)) as well as temperature change have been investigated on the micelle formation of SDS + OFC mixture. The micellization of SDS + OFC and TRX + OFC systems has been characterized by the determination of critical micelle concentration (CMC) from conductivity vs. SDS concentration (conductivity technique) and Absorbance vs log[TRX] (UV-Visible spectroscopic technique) plots respectively. The micellization of SDS was delayed owing to the introduction of the OFC drug while the effect has been intensified as a function of OFC concentration. At a fixed OFC concentration and temperature, the CMC values were acquired to be augmented with the upsurge of alcohol concentration. The enhancement of the CMC changes has been perceived with the escalation of temperature at a definite concentration of OFC in water and 5% (w/w) aq. alcohols media. The disfavor of micellization of TRX in aq. EtOH solutions in comparison to aqueous solution also detected from UV-Visible spectroscopic technique. The binding constant (Kb) for the complexation of TRX with OFC drug was determined using the Benesi-Hildebrand plot. The Kb values were obtained to be affected by the change of solvent and temperature. The negative free energy change (∆Gmo/ ∆Gbo) of the micellization and complexation demonstrate the spontaneous occurrence of micelle formation and complex development. The enthalpy changes (∆Hmo) of micellization were negative (exothermic process) and entropy changes (∆Smo) were positive (highly disordered and entropy-dominated micellization). Other thermodynamic properties ((∆Hbo and ∆Sbo) and thermodynamics of transfer) have been evaluated and illustrated as well, for the working systems. [Display omitted]